HUBUNGAN ANTARA PARENTING SELF-EFFICACY DENGAN FUTURE TIME PERSPECTIVE PADA IBU YANG MEMILIKI ANAK BERKEBUTUHAN KHUSUS - Rizka Andhika Fitriyah; Ratna Syifa’a Rachmahana (Universitas Negeri Makassar, 2020)
This study aims to determine the relationship between parenting self – efficacy and future time perspective among mother who have a special needs children. This research implicates 72 mother of special needs childern with a various kinds of special needs. The used scale to measure mother’s parenting self-efficacy is made by Coleman and Karraker (2000) called Self-Efficacy for Parenting Task Index or SEPTI. And the Future Time Perspective scale which is made based on the theory put forward by Nurmi (1989). The obtained data is analyzed using a software called SPSS version 22.0 for Windows. The result shows that there is a positive correlation between parenting self-efficacy and future time perspective among mothers with a special needs children (r = 0,610 with a sig (p) score = 0,00 (p < 0,05). Therefore, when the mother has a high level of parenting self- efficacy, her future time perspective will also be high.Keywords : Parenting Self-effcacy, Future Time Perspective, Mother With a Special Needs Childern.